2016
DOI: 10.1002/14651858.cd008858.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for preventing herpes zoster in older adults

Abstract: Analysis 5.3. Comparison 5 Live attenuated VZV zoster vaccine versus pneumo 23 vaccine, Outcome 3 41,650 pfu/dose. i Vaccines for preventing herpes zoster in older adults (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 69 publications
3
32
1
Order By: Relevance
“…Recently, a Cochrane review including 10 RCTs of live-attenuated zoster vaccine found that the pooled risk ratio for incident zoster up to 3 years post vaccination was 0.49 (95% C.I. 0.43 to 0.56) [81]. The zoster vaccine has not demonstrated major safety concerns.…”
Section: Development Of a Vaccine Against Zoster Efficacy And Safetymentioning
confidence: 99%
“…Recently, a Cochrane review including 10 RCTs of live-attenuated zoster vaccine found that the pooled risk ratio for incident zoster up to 3 years post vaccination was 0.49 (95% C.I. 0.43 to 0.56) [81]. The zoster vaccine has not demonstrated major safety concerns.…”
Section: Development Of a Vaccine Against Zoster Efficacy And Safetymentioning
confidence: 99%
“…The ZLAV efficacy was first demonstrated in the shingles prevention RCT, 88 by the Cochrane review that examined 4 placebo/vaccine studies, 89 and in a recent routine life cohort study. 90 The ZLAV reduced the zoster incidence with a risk ratio (RR) of 0.49 (95% CI 0.43-0.56).…”
Section: Zoster Vaccinationmentioning
confidence: 99%
“…92 Adverse drug reactions are mainly local at the injection site, without any serious adverse reactions. [88][89][90] An adjuvanted VZV gE subunit vaccine is being developed as a potential alternative to the currently approved ZLAV. A pivotal phase III study to assess the efficacy of the investigational vaccine for the prevention of shingles has met its primary endpoint and showed that HZ/su reduced the risk of shingles by 97.2% in adults aged 50 y and older compared with placebo.…”
Section: Zoster Vaccinationmentioning
confidence: 99%
“…The formulation is live-attenuated, which can prevent primary infection as well as reactivation in older adults [57]. Not yet available for clinical use is an adjuvanted recombinant subunit formulation [58]. Similar to the other HHVs, primary infection with varicella has been associated with CNS complications such as ataxia, encephalitis, stroke, meningitis, and Guillain-Barré syndrome [59].…”
Section: Vaccines Under Development For Human Herpesvirusesmentioning
confidence: 99%